Influence of global warming and human activity on mercury accumulation patterns in wetlands across the Qinghai–Tibet Plateau - Feng, Xinbin; Wang, Xun; Jia, Longyu; Yuan, Wei; Lu, Meng; Liu, Nantao; Wu, Fei; Cai, Xinyuan; Wang, Feiyue; Lin, Che-Jen (National Science Review, 2024)
ABSTRACT Wetlands in the Qinghai–Tibet Plateau are a unique and fragile ecosystem undergoing rapid changes. We show two unique patterns of mercury (Hg) accumulation in wetland sediments. One is the ‘surface peak’ in monsoon-controlled regions and the other is the ‘subsurface peak’ in westerly-controlled regions. The former is attributed to the combined effects of increasing anthropogenic emissions and climate-induced changes in the cryosphere and wetland hydrology in the last 100−150 years. The climate changes in westerly-controlled regions in the last 50−70 years led to a fluctuation in hydrology and Hg peak in the sediment subsurface. The increase in legacy Hg input from soil erosion has largely enhanced the Hg accumulation rate in wetlands since the 1950s, especially in the proglacial wetlands. We highlight that accelerated glacier melting and permafrost thawing caused by global warming have altered geomorphology and hydrology, and affected Hg transport and accumulation in wetlands.